Operationalizing adaptive team performance: design, validation, and application of instruments in law enforcement / Norsyazwani Ab Halim, Azlyn Ahmad Zawawi and Nur Zafifa Kamarunzaman - Ab Halim, Norsyazwani; Ahmad Zawawi, Azlyn; Kamarunzaman, Nur Zafifa (Faculty of Administrative Science and Policy Studies, 2025)
This paper presents the concept of adaptive team performance in the context of law enforcement, focusing on how teams can respond effectively to dynamic and often unpredictable challenges. Adaptive performance is important for teams that must make quick decisions, solve complex problems, and maintain effectiveness in high-pressure situations. Based on existing literature, this study identifies key dimensions of adaptive team performance, including handling emergencies, managing stress, solving problems creatively, dealing with uncertainty, training and learning efforts, interpersonal adaptability, cultural adaptability, and physical adaptability. It also explores the antecedents influencing adaptive behavior, such as individual characteristics, job autonomy, group dynamics, and organizational support. This study involves a review of selected literature to identify and synthesize relevant dimensions and antecedents of adaptive performance. The items from each adaptive performance dimension and antecedent were coded and subjected to thematic analysis to uncover underlying patterns and interrelationships. A systematic categorization of items was conducted, leading to the development of an adaptive performance framework. The adaptive performance framework focuses on key concepts from existing research to provide a comprehensive understanding of adaptive performance and how it can be fostered within organizations. This framework is particularly relevant for high-stakes environments like law enforcement, where adaptability is crucial for success.